Assessment of the efficiency of municipal companies based on local collective transport - Wąsowicz, Krzysztof (Journal of Public Governance, 2018)
The main objective of this article is to determine the effectiveness of enterprises providing municipal services and a model approach for processes related to the provision of local public transport services in Poland. In particular, the identification included methods of organisation and implementation of public utility tasks as well as organisational and legal forms and forms of ownership in the case of local collective transport. An attempt has been made to determine the effectiveness of enterprises providing urban transport services in cities in Poland, assessing their operational, financial, technical and social effectiveness.The research design and methods used in this article are based on the assessment of the effectiveness of enterprises using taxonomic methods of grouping e ntities according to selected characteristics and efficiency measures. The use of the k-means method with the number of clusters determined on the basis of the hierarchical Ward method, in which the contribution of variables to the differentiation of clusters was determined on the basis of a one-way analysis of ANOVA variance, to obtain groups of companies with similar efficiency indicators.The findings, based on the conducted research, present the relationship between the economic efficiency of public transport companies and their organisational and legal form as well as the type of ownership.Recommendations from empirical studies indicate that public enterprises operating in the field of municipal services provide public utility services with a higher level of economic efficiency than other distinctive groups of carriers.The added value is that the research methods presented in this work can be successfully applied to other sectors of the economy and other countries in order to verify the effectiveness of individual organizational, legal and ownership forms of enterprises.JEL classification: L300